Filsafat Positivisme Auguste Comte: Perdebatan Pemikiran dan Keberadaan Agama Positif - Hudri, Misbah (Aqlania, 2023)
Positivism as a philosophical movement has played a crucial role in the development of modern philosophy. Its existence marks a significant point in the discourse of philosophical scholarship. Essentially, this philosophical movement is quite old, known long before it was introduced by the figures discussed in this writing. The discussion in this writing aims to convey information about positivism in the style of Auguste Comte. In connection with the debates surrounding his thoughts, criticisms, or the search for positive aspects of positivism itself, it is important to note. Beyond that, an important aspect to be discussed is also related to the positive religion commonly known as "the humanity of religion." Of course, this 'religion' needs to be discussed further, considering that positivism highly values scientific knowledge and rejects anything unreal, such as metaphysics and beliefs that cannot be scientifically proven.. This research falls under the category of qualitative research, with its working instrument utilizing a descriptive-analytical method and involving a literature review. Auguste Comte, in the development of his thinking, is inseparable from his significant contribution to the advancement of positivism and sociology. Thus, he has had an impact on the fields of science and humanity. Positive religion, or the humanity of religion, understands that the highest morality in this new religion is love and devotion to humanity. From this understanding, the motto of positivism is born: "love as principle, order as basic, and progress as an end." Therefore, even though it is referred to as a religion at first glance, it is not detached from the foundational principles that Auguste Comte consistently upheld.